INADVERTENT INTRAOCULAR SURGERY IN CHILDREN WITH UNSUSPECTED RETINOBLASTOMA: A Study of 14 Cases. Issue 9 (September 2019) - Kaliki, Swathi; Taneja, Shikha; Palkonda, Vijay A. R.
Abstract : Purpose: To study the clinical presentation and treatment outcome of patients who underwent inadvertent intraocular surgery before the diagnosis of retinoblastoma. Design: Retrospective study of 14 patients who had undergone an inadvertent intraocular surgery before the diagnosis of retinoblastoma. Results: The mean age at presentation to the ocular oncology clinic was 69 months. The most common initial misdiagnosis was endophthalmitis (n = 4). The most common inadvertent intraocular surgeries were pars plana vitrectomy (n = 6) with/without lensectomy and evisceration with/without previous pars plana vitrectomy (n = 5). The mean interval between intraocular procedure and initiation of treatment for retinoblastoma was 7 months. At presentation in the oncology clinic, the tumor was intraocular (n = 3), with extrascleral tumor extension (n = 11), and/or optic nerve tumor extension (n = 5). All patients were started on multimodal treatment including 12 cycles of high-dose systemic chemotherapy, enucleation or orbital exenteration, and orbital external beam radiotherapy. Over a mean follow-up period of 27 months, 8 (57%) patients died because of progressive disease despite initiation of treatment. Conclusion: Misdiagnosis and inadvertent surgical intervention in cases of retinoblastoma in combination with delayed initiation of appropriate treatment is associated with poor prognosis. High index of suspicion for retinoblastoma is needed to avoid misdiagnosis and mismanagement. Abstract : Of the 14 patients who underwent inadvertent intraocular surgery before the diagnosis of retinoblastoma, 8 (57%) patients died despite initiation of intensive treatment indicating poor prognosis in such cases.